Endovascular Treatment for Acute Ischemic Stroke in Patients on Oral Anticoagulants: Results From the MR CLEAN Registry. Issue 6 (June 2020) - Goldhoorn, Robert-Jan B.; van de Graaf, Rob A.; van Rees, Jan M.; Lingsma, Hester F.; Dippel, Diederik W.J.; Hinsenveld, Wouter H.; Postma, Alida; van den Wijngaard, Ido; van Zwam, Wim H.; van Oostenbrugge, Robert J.; Roozenbeek, Bob
Abstract : Background and Purpose—: The use of oral anticoagulants (OAC) is considered a contra-indication for intravenous thrombolytics as acute treatment of ischemic stroke. However, little is known about the risks and benefits of endovascular treatment in patients on prior OAC. We aim to compare outcomes after endovascular treatment between patients with and without prior use of OAC. Methods—: Data of patients with acute ischemic stroke caused by an intracranial anterior circulation occlusion, included in the nationwide, prospective, MR CLEAN Registry between March 2014 and November 2017, were analyzed. Outcomes of interest included symptomatic intracranial hemorrhage and functional outcome at 90 days (modified Rankin Scale score). Outcomes between groups were compared with (ordinal) logistic regression analyses, adjusted for prognostic factors. Results—: Three thousand one hundred sixty-two patients were included in this study, of whom 502 (16%) used OAC. There was no significant difference in the occurrence of symptomatic intracranial hemorrhage between patients with and without prior OACs (5% versus 6%; adjusted odds ratio, 0.63 [95% CI, 0.38–1.06]). Patients on OACs had worse functional outcomes than patients without OACs (common odds ratio, 0.57 [95% CI, 0.47–0.66]). However, this observed difference in functional outcome disappeared after adjustment for prognostic factors (adjusted common odds ratio, 0.91 [95% CI, 0.74–1.13]). Conclusions—: Prior OAC use in patients treated with endovascular treatment for ischemic stroke is not associated with an increased risk of symptomatic intracranial hemorrhage or worse functional outcome compared with no prior OAC use. Therefore, prior OAC use should not be a contra-indication for endovascular treatment. Abstract : Supplemental Digital Content is available in the text.